Analisis Frasa dalam Teks Laporan Hasil Observasi pada Buku Ajar Bahasa Indonesia Kelas VIII SMP Kurikulum Merdeka - Muhammad Farchan Muntaha; Muhammad Thoriq Akbar; Rizqi Ardiansyah; Arif Setiawan; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Phrase is a part of grammatical that has several words which do not exceed the function limit. This research analyzes the phrases in the report text in the form of observation in the Indonesian language textbook for grade VII of the independent curriculum. This article is intended to realize the number of phrases in terms of word categories in the text of the report on observation in the Indonesian language textbook for class VIlI junior high school curriculum. The research technique used is qualitative descriptive technique. Data in this studies is in the form of phrases which are taken from the text of the observation report and analyzed according to the classification of phrases. The text listed was taken from the Indonesian language textbook for grade VIII of the independent curriculum junior high school with the year of publication, namely 2021. The method of collecting the results of this study by utilizing the observation technique and the simak catat method. The technique of analyzing data applied to analyze phrases in this research activity is a qualitative technique. Data assessment method is carried out by observation. The results of this study found 185 phrases consisting of 43 prepositional phrases, 55 noun phrases, 17 verb phrases, 7 adjective phrases, 12 numerical phrases, and 51 conjunction phrases. The benefits of this study can contribute to the field of language, especially in the field of syntax about the use of phrases in the text and as reference material for conducting language research.